EthNYcity : the nations, tongues, and faiths of metropolitan New York - Clayman, Chris; Lee, Meredith (New York, N.Y. : Metro New York Baptist Association ; Cary, N.C. : Baptist State Convention of North Carolina, 2010)
"... an important resource for all people interested in cross-cultural missions in North America. ... profiles on the most significant immigrant groups in metro New York. ... not New York City alone ... includes northern New Jersey, Long Island, parts of upstate New York, and parts of Connecticut."--back cover.
Includes bibliographical references (p. 180-187)
Keywords: Ethnic groups -- New York Metropolitan Area; Ethnic groups -- Missions -- New York Metropolitan Area; Immigrants -- New York Metropolitan Area; Immigrants -- Religious life -- New York Metropolitan Area; New York Metropolitan Area -- Ethnic relations